The inflected infinitive in the Romance languages - Scida, Emily, 1969- (Outstanding dissertations in linguistics., 2004)
This book investigates two prominent issues with regard to the inflected infinitive - the syntactic distribution of the Portuguese inflected infinitive, and its origin and development from Early Romance.